2018
DOI: 10.1002/ana.25209
|View full text |Cite
|
Sign up to set email alerts
|

The nerve conditioning lesion: A strategy to enhance nerve regeneration

Abstract: By altering the intrinsic metabolism of the cell, including the upregulation of regeneration-associated genes (RAGs) and the production of structural proteins for axonal outgrowth, the conditioning lesion sets up an environment highly conducive to regeneration. In this review, we assess 40 years of research to provide a comprehensive overview of the conditioning lesion literature, directed at (1) discussing the mechanisms of and barriers to nerve regeneration that can be mitigated by the conditioning lesion, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…The increased Luman expression and significantly increased intrinsic axon growth competence that we observed in neurons contralateral to 1-week injury support previous work by the Ryoke et al (60) showing that a prior lesion can serve to condition contralateral DRG to express higher levels of protective and growth-promoting compounds, and to regenerate more robustly when subsequently injured (61). Interestingly, we found the mode of axon growth to be predominantly of the elongating form typically associated with the 1-week injuryconditioned neurons (31), as opposed to the highly arborized outgrowth we observed for contralateral neurons at the 2 earlier timepoints, which did not differ from that observed for naïve neurons and is in agreement with that which we previously reported for neurons contralateral to 1-day injury (12).…”
Section: Implication Of the Contralateral Effectsupporting
confidence: 90%
“…The increased Luman expression and significantly increased intrinsic axon growth competence that we observed in neurons contralateral to 1-week injury support previous work by the Ryoke et al (60) showing that a prior lesion can serve to condition contralateral DRG to express higher levels of protective and growth-promoting compounds, and to regenerate more robustly when subsequently injured (61). Interestingly, we found the mode of axon growth to be predominantly of the elongating form typically associated with the 1-week injuryconditioned neurons (31), as opposed to the highly arborized outgrowth we observed for contralateral neurons at the 2 earlier timepoints, which did not differ from that observed for naïve neurons and is in agreement with that which we previously reported for neurons contralateral to 1-day injury (12).…”
Section: Implication Of the Contralateral Effectsupporting
confidence: 90%
“…As noted at the beginning of this review, although regeneration occurs in the PNS, it is slow and incomplete. It has been proposed recently that, if the molecular mechanism underlying the conditioning-lesion effect were understood, it might be possible to elicit this response via a non-destructive means and facilitate regeneration in patients soon after a peripheral nerve injury (Senger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of human nerve injuries, resulting from vehicle accidents, recreational activities and iatrogenic injuries during surgeries, occur in the upper extremity ( Figure 3A) [42]. Seminal studies in rodents in the Gordon and Brushart laboratories with Canadian and German collaborators [29,[43][44][45][46][47] (reviews [33,[48][49][50][51][52]), and in human patients in the Chan laboratory in Canada [53][54][55] (reviews [33,48,52,56]), demonstrated that brief low frequency, electrical stimulation of the nerve proximal to the site of transection and surgical repair, accelerated motor and sensory nerve regeneration. More recently, a positive conditioning effect of electrical stimulation of the intact nerve, prior to nerve transection and repair, has been pursued in rat studies in the laboratories of Chan and Webber [57][58][59][60].…”
Section: Promising Strategies To Improve Nerve Regenerationmentioning
confidence: 99%